Web-Based Sukaraja Puskesmas Services Governance Information System - Marlia Sari; Lusia Septia ER; Muhammad Rasid (bit-Tech, 2023)
The Community Health Center is a functional health organization which is a center for community health development which also fosters community participation in addition to providing comprehensive services to the community in its working area in the form of main activities. Currently, at the Sukaraja Community Health Center, all data recording is still done manually using paper media. Because increasingly modern technology requires Puskesmas as one of the health service providers to always improve the quality of its services. The use of computers to process data is very necessary because it can provide benefits and convenience in patient care. In this case, community health centers are required to always improve the professionalism of their employees and improve their health facilities or facilities to provide satisfaction to the community using health services. The objectives to be achieved are: Designing a website-based health center management information system, Improving the conventional health center service system with a computerized system. And makes it easier to process patient data for outpatient, inpatient, pharmacy, counter registration, administration (printing certificates/referrals & health center reports) and general clinics using the waterfall method. The stages of the waterfall method are Requirements, design, implementation, integration, Maintenance. The website-based governance information system that has been produced in this design can process patient data from outpatient, inpatient, emergency health centers and pharmacy services. With this website-based community health center management information system application, data at the Sukaraja Community Health Center is now integrated through a database so that it can process data effectively and efficiently and help provide good services.